2021
DOI: 10.35848/1347-4065/ac3026
|View full text |Cite|
|
Sign up to set email alerts
|

Fabrication of AlN templates by high-temperature face-to-face annealing for deep UV LEDs

Abstract: AlN templates fabricated via a combination of sputtering deposition and post-deposition high-temperature face-to-face annealing can be applied to deep-ultraviolet (DUV) light-emitting devices because of their extremely low threading dislocation density (TDD) despite their low-cost and simple fabrication process. First, this paper summarizes the overview and essential crystalline characteristics of the face-to-face annealed sputter-deposited AlN template (FFA Sp-AlN). Thereafter, recent progress in the TDD redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…During the HT recrystallization process, the high-density dislocations of the sputtered AlN annihilate, the domain boundaries disappear, and the surface transforms into to a step and terrace morphology. 21 Double sputtering and thermal cycle HTA were further proposed, and the TDD of Alpolar AlN film on sapphire was reduced to 2.4 × 10 7 cm −2 , 22 which is the best result reported so far. Room-temperature lasing of AlGaN-based UVB LDs grown on annealed sputtered AlN templates have been demonstrated.…”
Section: ■ Introductionmentioning
confidence: 85%
“…During the HT recrystallization process, the high-density dislocations of the sputtered AlN annihilate, the domain boundaries disappear, and the surface transforms into to a step and terrace morphology. 21 Double sputtering and thermal cycle HTA were further proposed, and the TDD of Alpolar AlN film on sapphire was reduced to 2.4 × 10 7 cm −2 , 22 which is the best result reported so far. Room-temperature lasing of AlGaN-based UVB LDs grown on annealed sputtered AlN templates have been demonstrated.…”
Section: ■ Introductionmentioning
confidence: 85%
“…Recently, a new approach to the fabrication of low-dislocation AlN buffer layers was developed, based on high-temperature face-to-face annealing (HT-FFA) [ 45 , 46 ]. The starting point of the technique is the deposition of poly-crystalline AlN on c-plane sapphire substrates by radio-frequency sputtering of either sintered AlN or high-purity Al targets in the N 2 ambience (the choice of the target controls the dominant polarity of the sputtered film [ 46 ]). Then, two wafers prepared by sputtering were placed face-to-face together and annealed at temperatures of 1600–1750 °C for up to 48 h in N 2 environment.…”
Section: Materials Quality and Its Impact On Internal Quantum Efficie...mentioning
confidence: 99%
“…The HT-FFA technique provided AlN templates with TDD as low as 2 × 10 8 cm −2 . Further TDD reduction to 1.5 × 10 8 cm −2 was accomplished by using thermo-cycling during the annealing stage [ 46 ]. The use of double HT-FFA with a second AlN film deposition on the already annealed template followed by a secondary annealing resulted in the reduction of TDD down to 4.3 × 10 7 cm −2 [ 46 ].…”
Section: Materials Quality and Its Impact On Internal Quantum Efficie...mentioning
confidence: 99%
“…Additionally, the previously found AlN growth is low growth temperature for AlN material, and it is not verified as reducing the growth rate by typical desorption as observed in other materials 20 . Meanwhile, Miyake et al reported low dislocation AlN growth by the sputter-anneal method, which method realized high-temperature with the temperature of 1700 °C by separating in AlN deposition and crystallization 21 , 22 . However, this approach cannot be continuously grown in the device structure and requires renewal by eliminating it from the chamber.…”
Section: Introductionmentioning
confidence: 99%